Factors associated with relapse in schizophrenia despite adherence to long-acting injectable antipsychotic therapy. (July 2016) - Alphs, Larry; Nasrallah, Henry A.; Bossie, Cynthia A.; Fu, Dong-Jing; Gopal, Srihari; Hough, David; Turkoz, Ibrahim
Abstract : Many patients with schizophrenia will relapse despite uninterrupted antipsychotic (AP) long-acting therapy (LAT). This exploratory analysis examined variables associated with relapse despite ensured adherence to LAT. This was a post-hoc exploratory analysis of a 1-year study of risperidone long-acting injection in patients with stable schizophrenia or schizoaffective disorder (NCT00297388; N =323). Patients were discontinued from previous oral APs and randomly assigned to biweekly intramuscular injections of risperidone long-acting injectable 50 ( n =163) or 25 mg ( n =161) for 52 weeks. Cox proportional hazards regression models examined variables putatively associated with relapse. A total of 59/323 (18.3%) patients relapsed over 12 months despite continuous AP LAT. Variables associated with the risk of relapse included illness duration (6.0% increase each year; P =0.0003) and country (Canada vs. USA, 4.7-fold risk increase; P =0.0008). When illness duration was further categorized as ⩽5, 6–10, and >10 years, patients with an illness duration of >10 versus ⩽5 years were at greatest risk of relapse (>10 vs. ⩽5 years associated with a 4.4-fold increase in the risk of relapse; P =0.0181). Findings suggest that patients with more chronic illness have a greater risk of relapse despite ensured treatment adherence, supporting the need for early intervention to prevent the deleterious effects of chronicity.